Is the 1:4 elutriation ratio reliable? Ecotoxicological comparison of four different sediment:water proportions - ARIZZI NOVELLI A.; LOSSO C.; TAGLIAPIETRA D.; PANTANI C.; LIBRALATO, Giovanni; VOLPI GHIRARDINI, Annamaria (Ecotoxicology and Environmental Safety, 2006)
Methodological research was carried out to evaluate the discriminatory capability of three toxicity bioassays toward different elutriation ratios (1:4, 1:20, 1:50, and 1:200 sediment:water ratios). Samples from six sampling stations of the Lagoon of Venice have been investigated. The toxicity bioassay results (sea urchin Paracentrotus lividus Lmk sperm cell and embryo toxicity bioassays and bivalve mollusk Crassostrea gigas Thunberg embryo toxicity bioassays) have shown that elutriates generated from the widely used 1:4 ratio were less toxic than those from intermediate ratios (1:20 and 1:50).